Aspectos relacionados à gênese do comportamento infracional do adolescente: revisão integrativa de literatura - Peres, Tacyana Silva (2021)
To understand the adolescent who commits an infraction, it is necessary to understand the factors that influence his life, the environment in which he lives and the experiences that will build his subjectivity and, consequently, his conduct. Therefore, this research seeks to understand the influences related to the practice of acts contrary to the Law by adolescents, through the identification in the literature of possible causes related to the emergence of infraction behavior in adolescence. From an integrative literature review, a bibliographic search was performed in electronic databases (SCOPUS, Web of Science, PsycINFO, CINAHL, LILACS, SCIELO) by crossing the keywords “Juvenile Delinquency” AND “Reasons” and “Juvenile Delinquency” AND “Causes”. The search was guided by the question: “What are the causes related to the emergence of the infraction behavior”, elaborated according to the PICo strategy (Population or Problem / Population or Problem, Interest / Phenomena de Interesse e Context / Contexto). Only articles published in Portuguese, English and Spanish were included. As a result, 42 studies were identified, of which 20 were repeated and 11 were excluded after reading the titles and abstracts for not meeting the inclusion criteria, totaling 11 articles at the end. The research presented was organized in tables to facilitate the analysis. Then, there was a complete reading of the articles, for the exploratory analysis, four thematic axes to be discussed are identified: personal, family, school and social as influential phenomena in the causes related to the infraction behaviors. The results of this research point to a prevalence of studies on social aspects as the main causes in influencing offending behaviors and the significant relationship between the environment and peers that these adolescents live with, in addition to being stimulated by ideologies of the media and entertainment. It is perceived that a large part of the difficulties faced by adolescents is related to the process of identifying and building their self-concept and self-image, which demonstrates a direct relationship with infringing behaviors. Still, the adolescents' social behaviors come from the relationships established in the family context, which becomes a point of reference in the formation of their children, guidance on social behaviors and also in the sense of strengthening affective bonds, which reinforces that family relationships they are established as an important risk or protection factor for the possible infractions of adolescents. Finally, it was identified that adolescents who show disinterest in what the school wants to teach, can lead to school dropout or low schooling and be a causal relationship of criminal practices. Therefore, it is understood that there is a need to develop effective strategies for intervention and prevention in the care of adolescents in conflict with the law. Keywords: Juvenile delinquency. Teenager in conflict with the law. Causality. Review.